2017
DOI: 10.1007/s10567-017-0249-y
|View full text |Cite
|
Sign up to set email alerts
|

Alliance and Treatment Outcome in Family-Involved Treatment for Youth Problems: A Three-Level Meta-analysis

Abstract: Alliance has been shown to predict treatment outcome in family-involved treatment for youth problems in several studies. However, meta-analytic research on alliance in family-involved treatment is scarce, and to date, no meta-analytic study on the alliance–outcome association in this field has paid attention to moderating variables. We included 28 studies reporting on the alliance–outcome association in 21 independent study samples of families receiving family-involved treatment for youth problems (N = 2126 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 85 publications
(163 reference statements)
0
27
0
Order By: Relevance
“…The increased resistance to treatment and to change may require more time and effort to form a strong alliance with the involuntary group (Snyder & Anderson, ). Results of two recent meta‐analyses suggested that mandated status moderates the alliance‐outcome correlation for youth mandated to attend therapy (McLeod, ; Welmers‐van de Poll et al, ).…”
Section: Background and Significancementioning
confidence: 99%
“…The increased resistance to treatment and to change may require more time and effort to form a strong alliance with the involuntary group (Snyder & Anderson, ). Results of two recent meta‐analyses suggested that mandated status moderates the alliance‐outcome correlation for youth mandated to attend therapy (McLeod, ; Welmers‐van de Poll et al, ).…”
Section: Background and Significancementioning
confidence: 99%
“…Alliance consists of the affective and collaborative aspects of a client–therapist relationship and is usually conceptualized as personal alliance (the affective bond) and task-related alliance (addressing the goals of the treatment and the tasks required to achieve those goals; Bordin, 1979 ; Hougaard, 1994 ). A strong alliance is associated with positive treatment outcomes and higher client satisfaction in a wide range of psychotherapeutic interventions, such as individual child, adolescent and adult psychotherapy, family-based or systemic therapy, and parenting interventions (de Greef et al, 2017 ; Friedlander et al, 2018 ; Karver et al, 2018 ; Welmers-van de Poll et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we thus focused on predicting both family members' and therapists' experiences of the alliance. Because we were interested in alliance as a dynamic process that develops over time (Horvath, 2011;Welmers-van de Poll et al, 2018), we investigated mid-treatment alliance, taking into account the possible effects of early treatment therapist behavior and alliance.…”
Section: Present Studymentioning
confidence: 99%
“…Alliance is generally defined as a professional relationship between a therapist and his or her client, consisting of an emotional bond and agreement on what goals and tasks should be central during treatment (Bordin, 1979;Elvins, & Green, 2008). It has shown to be a significant contributor to psychotherapy outcome in adults, youth and families (Flückiger et al, 2018;Murphy & Hutton 2018;Welmers-van de Poll et al, 2018). However, several studies have shown that therapists differ substantially in how much they succeed in building alliances with their clients (Dinger et al, 2008;Nissen-Lie et al, 2010).…”
Section: Introductionmentioning
confidence: 99%